Study of low plasticity clay for optimum dosage of the soil-cement (2019)
The need to improve people's living conditions starts from the reality of the durability of rural road constructions, which have a short useful life and have a negative impact on the inhabitants of these regions. This project aims to improve access to rural areas, rural economic development and thus improve the quality of life of people in the sector; taking into account that at the moment of building a rural road, has a better resistance and durability in time, this was done by analyzing the properties of the clay mixture of low plasticity in the dosage of soil-cement that were tested by tests to determine the liquid limit of soils, determination of the plastic limit, plasticity index, moisture test, classification of soil by sieving, granulometric analysis, unit weight-humidity relations in soils, soil support relationship in the laboratory; in order to find the best dosage that provides greater strength, long-term durability and risk reduction. The results indicate that this type of clay requires an improvement with cement, due to its bearing capacity of 2% and 4%, which gives it a very poor quality to be used in the construction of rural roads.